Educação escolar de indígenas surdos: Um olhar para o contexto Apinajé - Barroso, Fabiane Silva (Universidade Federal do Tocantins, 2022)
This work is an ethnographic bibliographic research on the school reality education experienced by the deaf indigenous peoples of the Apinajé people in northern of Tocantins. Our main objective was to understand the school education process of Brazilian deaf indigenous peoples. For this, we use the mapping of theses and dissertations about deaf indigenous peoples produced in Brazil in recent decades. The two specific objectives sought, respectively, i) to describe how is the school education of deaf Apinajé indigenous peoples; ii) in order to provide supplies for the improvement of school education of deaf indigenous peoples in the Tocantins state. Therefore, we conclude that of the seven deaf indigenous peoples, only two are actually enrolled in indigenous schools. However, the fact that they are enrolled does not guarantee access to school education. It is worth saying that the school education model implemented in the educational process of other peoples who also have deaf indigenous peoples may not meet the specific needs of the Apinajé people. In this sense, we seek to present insums that attest to the importance of learning Libras, from contact between deaf people to the development of their identity, on the need to register the possible Apinajé sign language, and also emphasize the legal contributions that endorse the multilingual creation class for the deaf apinajé indigenous.